Nash equilibria of COVID-19 vaccination - Alessandro Saccal (Economics and Econometrics Research Institute (EERI), 2022)
The present research conducts a formal analysis of the interactive decisions concerning the enterprise of COVID-19 vaccination on the part of governments and citizens. It specifically constructs a noncooperative static game with complete information between the citizen and the government encompassing the strategies of vaccination and no vaccination with regard to the former and the strategies of direct imposition, subsistence restrictions, luxury restrictions and no imposition with regard to the latter. On account of its payoff structure the present analysis finds that the game in question presents one sole and strict pure strategy Nash equilibrium, being that of strategies no vaccination and no imposition, respectively. The core rationale is that the citizen accepts COVID-19 vaccination only if his subsistence survival is placed at risk, because of the inherent unlawfulness presented by COVID-19 vaccination, itself due to foetal exploitation and potentially adverse effects, thereby prompting the government not to impose it, lest individual integrity and societal rights be violated as well. It furthermore shows that the exogenous elimination of the no imposition strategy on the part of the government transforms the Nash equilibrium into that of strategies vaccination and direct imposition, respectively, as materially come to pass. It finally determines that the unlikely addition of the revolution strategy on the part of the citizen in the presence of the elimination of the no imposition strategy on the part of the government likewise admits one sole and strict pure strategy Nash equilibrium, either in strategies vaccination and direct imposition or in strategies revolution and direct imposition, respectively.
Keywords: C72; D74; I12; I18; 330; citizen; COVID-19; equilibrium; game; government; imposition; pandemic; payoff; vaccination